2004
DOI: 10.1111/j.1365-2672.2004.02189.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of human faecal flora-associated mouse model for evaluation of the functional foods

Abstract: Aims: Animal models are required for evaluation of the functional foods such as pro/prebiotics exerting effects through the metabolism of the intestinal microflora. The object of this study was to establish new human floraassociated mice reflecting the environment of the human intestinal tract. Methods and Results: We inoculated a human faecal suspension into segmented filamentous bacteria (SFB) monoassociated mice as a model system. In both human flora (HF) and SFB-associated mouse (HF-SFB mouse), intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 38 publications
1
25
1
2
Order By: Relevance
“…HFA mice have been exploited and used as a tool reflecting human intestinal microbial ecology (6,7,30). Although the development of intestinal microbiota in HFA mice has been revealed by culture methods (12), there are few reports of the use of molecular methods (5,7,15). Our work has revealed the movement and persistence of human intestinal microbiota in formerly germfree mice by T-RFLP analysis.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…HFA mice have been exploited and used as a tool reflecting human intestinal microbial ecology (6,7,30). Although the development of intestinal microbiota in HFA mice has been revealed by culture methods (12), there are few reports of the use of molecular methods (5,7,15). Our work has revealed the movement and persistence of human intestinal microbiota in formerly germfree mice by T-RFLP analysis.…”
Section: Discussionmentioning
confidence: 88%
“…These limitations include differences in enzyme activity, concentrations of putrefactive products, and immunological activation by the composition of fecal bacteria (13,15). Previous studies reported that 60% to 80% of the observable bacteria in human intestines could not be cultivated (10,37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such HFA animal model has significantly facilitated progress in researches of human gut ecology, metabolism and immunity (Hazenberg et al, 1981;Roland et al, 1996;Oozeer et al, 2002;Gerard et al, 2004;Wilcks et al, 2004). However, owing to the significant differences in basic anatomy and physiology of rodents to human, key members of human gut microbiota such as bifidobacteria do not colonize the rodent gut; and rodents do not develop a full repertoire of immune responses unless some rodent-specific gut bacteria are reintroduced back into the gut (Raibaud et al, 1980;Imaoka et al, 2004). Thus, results obtained from these mice/rat models often have low relevance to human beings.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained from experiments on conventional animals may not be applicable to the human gut ecosystem, because the microflora of these animals differs in composition from that of humans (34). The lactobacilli is a major group in the intestinal microbiota of mice (35), which is not the case in humans where lactobacilli regularly are present but in a smaller proportion of the microflora (36,37).…”
Section: Discussionmentioning
confidence: 99%